Experimental investigation of maldistribution characteristics of gas‐liquid two-phase flow in a horizontal pipeline - Wei, Na; Jiang, Lin; Fan, Shuanshi; Liu, Anqi; Li, Haitao; Zhang, Shenghui; Zhang, Chao; Xue, Jin (Frontiers in Earth Science, 2022)
In the flow distribution of oil and gas gathering and transportation system, the flow pattern, inertia force, gravity, and other factors will lead to uneven flow distribution of each outlet pipe, which will seriously affect the economy and safety of the gathering and transportation system. Therefore, it is of great significance to analyze the characteristics of gas–liquid two-phase flow in horizontal pipelines. For this reason, an experimental device for maldistribution control of gas–liquid two-phase flow is developed in this article. In order to solve the problem of flow maldistribution in gas–liquid two-phase flow pipe, the test experiments of maldistribution control under the conditions of three flow patterns (stratified flow, slug flow, and annular flow) are carried out. Through experiments, we revealed the control law of flow pattern to liquid maldistribution and gas maldistribution with or without flute pipes and formed the maldistribution control scheme of gas–liquid two-phase flow in the horizontal pipeline. It is found that it is more beneficial to the control of average liquid maldistribution degree under the condition of slug flow pattern in horizontal manifold without flute pipe, and it is more beneficial to the control of average gas maldistribution degree under the condition of annular flow pattern without flute pipe. Without the function of the flute pipe and in the annular flow pattern, it is beneficial to the control of average maldistribution degree of gas–liquid two-phase flow. The findings of this research can be used as a reference for the field maldistribution control of oil and gas gathering and transportation systems.